C reactive protein, metabolic syndrome and cardiovascular risk in the Costa Rican population born between 1945 and 1955 (UNED Research Journal, 2020)
ABSTRACTIntroduction: Several studies have mentioned that there is a relationship between C reactive protein (CRP) and the metabolic syndrome (MS) and that this protein is a risk factor of cardiovascular disease. Objective: We studied the relationship of CRP with MS in the Costa Rican population. Methods: People born in Costa Rica between 1945 and 1955 were included in the study (n = 2273). MS was adapted according to the American Heart Association and National Heart, Lung and Blood Institute definition. Results: The prevalence of MS increased with elevated CRP levels (p < 0,001) and was higher in women (p < 0,001). CRP was independently and positively associated to waist circumference and negatively associated to HDL-cholesterol. The strongest CRP determinant was waist circumference (PSup = 67,8). After adjustment for age, sex, residence area, smoking and alcohol, in the highest quartile of CRP levels (CRP > 4 mg/L), the risk for MS was higher compared with that in the lowest quartile of CRP levels. Cardiovascular risk was higher in people with high levels of CRP. Conclusions: CRP levels is associated with the MS among the born between 1945 and 1955 Costa Rican population. Other studies are necessary to establish the role of CRP in the development of MS and cardiovascular events among Costa Rican population
Keywords: C reactive protein; metabolic syndrome; cardiovascular disease; risk factor; central obesity; Costa Rica